POSSIBILITIES OF IMPROVEMENT THE PREPAREDNESS OF OFFICERS OF THE BORDER CONTROL AND IMMIGRATION CONTROL STRUCTURAL UNITS OF THE STATE BORDER GUARD FOR SCHENGEN EVALUATION ON-SITE VISITS - Arbidāne, Iluta; Kuprijanova, Jekaterina; Garjāns, Juris; Pokule, Viktorija (Border Security and Management, 2016)
The aim of the research is evaluation of the present situation in Latvia concerning the preparedness of officers of the border control and immigration control structural units of the State Border Guard for Schengen evaluation on-site visits, examination of its legal regulation and practical aspects. In the research the scientific information about the Schengen evaluation historical development is summarised, its principles and mechanisms are reviewed, as well as its significance in the state border security is defined. The topicality of the theme is defined by the fact that in Latvia the regular Schengen acquis application evaluation started in July 2012 and it completed in May 2013. In practice the Member States’ evaluations are implemented on the basis of multiannual and annual evaluation programme. The next planned evaluation is foreseen in 2018. The new evaluation mechanism gave the possibility of organisation of unannounced evaluation on-site visits aiming at getting clearer picture of the present situation and working out recommendations for further actions to remedy any deficiencies in the external border control. It is obvious that the largest responsibility in Schengen acquis application enters the scope of competences of the institutions subordinate to the Ministry of the Interior, namely, the State Police and the State Border Guard. The issues of the research indicate how important and necessary is the complex approach to ensuring of Schengen evaluation on-site visits – both announced and unannounced – implementing the integrated border management in the general context of the European Union and contributing to the common state security in the European Union. In the research it was concluded that the State Border Guard implements a range of actions in accordance with its competence in the field in question, thus ensuring realisation of requirements on the corresponding level.